Ovarian cysts disappear after 14-day oral regimen of Korean red ginseng extract in letrozole-induced polycystic ovarian syndrome - Niknaz Moradi; Sepideh Arbabi Bidgoli; Shahla Chaichian (Korean Society of Obstetrics and Gynecology, 2021)
Objective Hormonal and inflammatory mechanisms are involved in the pathogenesis of polycystic ovarian syndrome (PCOS), which is a prevalent metabolic disorder among women of reproductive age. We aimed to evaluate the comparative efficiency of short-term oral administration of Korean red ginseng extract (KRGE) and the standard treatment on PCOS by focusing on the histopathological parameters and serum levels of luteinizing hormone (LH), follicle-stimulating hormone (FSH), testosterone, and nuclear factor kappa B (NF-κB). Methods A PCOS rat model was established by oral gavage of letrozole (1 mg/kg) for 21 days. The serum levels of LH, FSH, testosterone, and NF-κB were measured, and the morphological features and differences of the ovaries were examined in each group using a light microscope before and after 14 days of treatment with oral regimens-KRGE, oral contraceptives (OCPs), KRGE+OCPs, and carboxymethyl cellulose (CMC). Results OCPs alone could not normalize the mean ovarian weights of PCOS rats despite the 14-day oral regimen, but they were more effective in reducing the number and size of cysts compared to others. KRGE alone and in combination with OCPs was effective in normalizing abnormal ovarian weights, decreasing LH serum levels, and dissipating the ovarian cysts in PCOS rats. However, when combined with the standard regimen, KRGE showed additional therapeutic effects by efficiently reducing serum testosterone and NF-κB levels. Conclusion Our necropsy and histopathological evidence suggests the efficacy of KRGE as a novel integrative medicine against abnormal multiple follicular cysts. However, antiandrogenic and anti-inflammatory effects were only seen in animals that were administered a combination of KRGE and the standard regimen.